Characterizing Enterotypes in Human Metagenomics: A Viral Perspective - Song, Li; Zhang, Lu; Fang, Xiaodong (Frontiers in Microbiology, 2021)
The diversity and high genomic mutation rates of viral species hinder our understanding of viruses and their contributions to human health. Viral enterotypes as a description of the gut virome, its characteristics have not been thoroughly studied. Here we investigated the human gut virome composition using previously published sequencing data of 2,690 metagenomes from seven countries with various phenotypes. We found that the virome was dominated by double-stranded DNA viruses in our data, and young children and adults showed different stages in their fecal enterovirus composition. Beta diversity showed there were significantly less homogeneous in individuals with severe disorders of bile acid secretion, such as cirrhosis. In contrast, there were no significant differences in lengths to centroids or viral components between patients with phenotypes unrelated to bile acid, such as hypertension. Enterotypes determined independently from various projects showed similar specific viruses and enrichment direction. Confounding factors, such as different sequencing platforms and library construction, did not confuse enterotyping. The gut virome composition pattern could be described by two viral enterotypes, which supported a discrete, rather than a gradient, distribution. Three main components, enterotype 1 and 2 specific viruses and the other, comprise the total viral variation in these sets. Compared with enterotype 2, enterotype 1 had a higher viral count, Shannon index, and similarity between samples. The relative abundance of enterotype-specific viruses is a crucial determinant of enterotype assignment. Samples not matching any of the defined enterotypes in the database did not necessarily correlate to sickness. Therefore, the background context must be carefully considered when using a viral enterotype as a feature for disease prediction. Our results highlight important insights into the human gut virome composition by exploring two-main viral enterotypes in population and providing an alternate covariate for early disease screening.